2019
DOI: 10.5194/acp-19-11791-2019
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of PM<sub>2.5</sub> in eastern China due to regional-scale emission control: evidence from SORPES in 2011–2018

Abstract: Abstract. Haze pollution caused by PM2.5 is the largest air quality concern in China in recent years. Long-term measurements of PM2.5 and the precursors and chemical speciation are crucially important for evaluating the efficiency of emission control, understanding formation and transport of PM2.5 associated with the change of meteorology, and accessing the impact of human activities on regional climate change. Here we reported long-term continuous measurements of PM2.5, chemical components, and their precurso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(115 citation statements)
references
References 53 publications
3
109
0
3
Order By: Relevance
“…Elevated PM 2.5 is a major factor controlling regional climate and human health (van Donkelaar et al 2010;Yu et al 2014;Wang et al 2014a;Rosenfeld et al 2019;Pope 2000;Seinfeld and Pandis 2016;Chen et al 2013). The main driver of decreases in PM 2.5 in China between 2013 and 2017 was strict emission control policies (Zhang et al 2019;Ding et al 2019). Efforts to improve air quality during large international events, such as the 2008 Beijing Olympics, the 2014 Beijing Asia-Pacific Economic Cooperation (APEC) summit, the 2015 Grand Military Parade, and the 2016 Hangzhou G20 summit, have included short-term closure of power plants and factories, restriction of traffic, and reduction in construction activities (Xing et al 2011;Liu et al 2016;Li et al 2017;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated PM 2.5 is a major factor controlling regional climate and human health (van Donkelaar et al 2010;Yu et al 2014;Wang et al 2014a;Rosenfeld et al 2019;Pope 2000;Seinfeld and Pandis 2016;Chen et al 2013). The main driver of decreases in PM 2.5 in China between 2013 and 2017 was strict emission control policies (Zhang et al 2019;Ding et al 2019). Efforts to improve air quality during large international events, such as the 2008 Beijing Olympics, the 2014 Beijing Asia-Pacific Economic Cooperation (APEC) summit, the 2015 Grand Military Parade, and the 2016 Hangzhou G20 summit, have included short-term closure of power plants and factories, restriction of traffic, and reduction in construction activities (Xing et al 2011;Liu et al 2016;Li et al 2017;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The area with the most enhanced concentration of PM 2.5 was the north Zhejiang Plain, the Shanghai Municipality and the southern region of Jiangsu Province, where anthropogenic emissions contributed the most to air pollution [51]. Since 2013, the Chinese government intended to mitigate severe air pollution across the nation, and the Air Pollution Prevention and Control Action Plan (also called the Ten Measures of Air) was released [70]. These improving trends suggested that series of strict air pollution control policies and measures had indeed taken effect, as these actions included energy conservation, the promotion of cleaner fuels and the optimization of the industrial structure.…”
Section: Spatiotemporal Dynamicsmentioning
confidence: 99%
“…Although stringent pollution control measures have been implemented regarding factories, motor vehicles still discharge large amounts of primary pollutants into the atmosphere, including NO x , HC, VOCs, and CO. Under high solar radiation and temperature levels in summer, photochemical processes are prominent, contributing to a high O 3 concentration along with many highly reactive radicals, which further enhance the oxidizing capacity of the atmosphere (Frischer et al, 1999;Sharma et al, 2013). Haze pollution under a high atmospheric oxidation capacity had likely occurred on 22 and 26-27 July.…”
Section: Typical Air Pollution Episodes In Summer In Beijingmentioning
confidence: 99%
“…Due to a series of stringent emission control measures (China's State Council 2013 Action Plan for Air Pollution Prevention and Control available at http://www.gov.cn/ zhengce/content/2013-09/13/content_4561.htm, last access: 13 April 2020), including shutting down heavily polluting factories and replacing coal with clean energy sources, the annual mean PM 2.5 (particulate matter with a dynamic equivalent diameter smaller than 2.5 µm) concentration in major regions, especially in Beijing, has continuously decreased in recent years Ding et al, 2019). However, the ground-level O 3 concentration across China has increased rapidly in recent years, especially in summer, despite recent reductions in SO 2 and nitrogen oxide (NO x ) emissions (Chen et al, 2018;Anger et al, 2016;Wang et al, 2018;T.…”
Section: Introductionmentioning
confidence: 99%